Improving Pro-Sustainable Customer Responses Through Spiritual Marketing - Khalid Kadhim Mohammed (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
The purpose of this section is to reveal the role of spiritual marketing in enhancing customers' pro-sustainability response among a sample of visitors to religious tourist sites in Karbala (the cities of Sayyid al-Awsiya and al-Za'ir). This objective stems from a key research question: "Can spiritual marketing be employed to improve customers' pro-sustainability response among the studied sample?" To address this problem, the research adopted a questionnaire as a tool to identify the root causes of the issue. Customers demonstrated significant cooperation in responding to the questionnaire items, resulting in the collection of 397 customer opinions regarding the services provided in the cities of Sayyid al-Awsiya and al-Za'ir in Karbala Governorate. The descriptive-analytical approach was adopted to interpret the items and dimensions of the study topics. Accordingly, the research employed several tests to analyze the results using SPSS and AMOS (Version 28). The most important finding is that spiritual marketing is closely linked to and has a strong influence on customers' pro-sustainability response among visitors to the cities of Sayyid al-Awsiya and al-Za'ir in Karbala Governorate. This finding motivated the studied sample. On developing its internal capabilities and providing services that offer means of luxury and excellence compared to its counterparts in the region.